Cost of conducting Measles-Rubella vaccination campaign in India. Issue 1 (31st December 2022) - Chatterjee, Susmita; Song, Dayoung; Das, Palash; Haldar, Pradeep; Ray, Arindam; Brenzel, Logan; Boonstoppel, Laura; Mogasale, Vittal
ABSTRACT: A Measles-Rubella (MR) vaccination campaign was launched in India in a phased manner in February 2017 to cover children aged 9 months to 15 years. As evidence on campaign vaccine delivery costs is limited, the delivery cost for MR campaign from a government provider perspective was estimated in four Indian states, namely, Assam, Gujarat, Himachal Pradesh, and Uttar Pradesh. Costs were calculated in top-down and bottom-up approaches using data collected from 84 sites at different administrative levels and immunization partners in the study states from August 2019 to March 2020. All costs were presented in 2019 US and Indian Rupee (INR). The financial cost per dose of the MR campaign including all partner support ranged from US0.16 (INR 10.95) in Uttar Pradesh to US0.34 (INR 24.13) in Gujarat. In Uttar Pradesh, the full economic cost per dose was US0.87 (INR 61.39). The key financial cost drivers were incentives related to service delivery and supervision, the printing of reporting formats for record-keeping, social mobilization, and advocacy. The financial delivery cost per dose estimated was higher than the government pre-fixed budget per child for the MR campaign, probably indicating an insufficient budget. However, the study found underutilization of MR budget in two states and use of other sources of funding for the campaign indicating the need for proper utilization of the campaign budgets by the states. Unit cost information generated from this study will be useful for planning, cost projections, and economic analysis of future vaccination campaigns in India.